Enhancing Ciprofloxacin Removal: Unveiling the Potential of Graphene Oxide Synthesized from Cassava Peels through Box-Behnken Design Optimization - Rinawati Rinawati; Buhani Buhani; Widiarti Widiarti; Ahmad Isro; Elsa Fitrianingsih; Anisa Rahmawati; Agung Abadi Kiswandono; Fidelis Nitti (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
The adsorption of ciprofloxacin from an aqueous solution using graphene oxide as an adsorbent derived from cassava peel waste using a modified Hummers method was described. The properties of the adsorbent were characterized using Fourier-Transform Infrared Spectroscopy, X-ray diffraction, Raman Spectroscopy and Scanning Electron Microscopy-Energy Dispersive X-ray techniques. The influence of the operational variables including potential of hydrogen, adsorbent mass, and contact time in the adsorption of ciprofloxacin was evaluated by response surface methodology. In particular, the interactions between the operational variables were evaluated using the Box-Behnken Design to determine the optimum conditions. The results indicated that the optimum conditions were achieved at pH 3, contact time of 20 minutes, using 35 mg of graphene oxide adsorbent, resulting in an adsorption efficiency of 91.71%. The results demonstrated that the graphene oxide material derived from cassava peel waste can be effectively used as an adsorbent for ciprofloxacin from aqueous solutions.